Multiple Roles of the Polycistronic Gene Tarsal-less/Mille-Pattes/Polished-Rice During Embryogenesis of the Kissing Bug Rhodnius prolixus - Tobias-Santos, Vitória; Guerra-Almeida, Diego; Mury, Flavia; Ribeiro, Lupis; Berni, Mateus; Araujo, Helena; Logullo, Carlos; Feitosa, Natália Martins; de Souza-Menezes, Jackson; Pessoa Costa, Evenilton; Nunes-da-Fonseca, Rodrigo (Frontiers in Ecology and Evolution, 2019)
Genes encoding small open-reading frames (smORFs) have been characterized as essential players of developmental processes. The smORF tarsaless/mille-pattes/polished-rice has been thoroughly investigated in holometabolous insects, such as the fruit fly Drosophila melanogaster and the red flour beetle Tribolium castaneum, while its function in hemimetabolous insects was only recently investigated. Thus, we analyzed the function of the tal/pri/mlpt ortholog in a hemimetabolous insect, the kissing bug Rhodnius prolixus (Rp). Sequence analysis shows that Rp-mlpt polycistronic mRNA encodes two small peptides (11 to 14 amino acids) containing a LDPTG motif. Interestingly, a new hemipteran-specific conserved peptide of approximately 80 amino acids was also identified by in silico analysis. In silico docking analysis supports the binding of the small Mlpt peptides to the transcription factor Shavenbaby. Rp-mlpt in situ hybridization and knockdown via RNA interference showed a conserved role of Rp-mlpt during embryogenesis, with a major role in the regulation of thoracic versus abdominal segmentation, leg development and head formation. Altogether, our study shows that mlpt segmentation role is conserved in the common ancestor of Paraneoptera and suggests that polycistronic genes might generate order specific smORFs.